Разработка универсальной модели кинетики стационарного процесса биоочистки с субстратным ингибированием - Бахарева, Анна Юрьевна; Шестопалов, Алексей Валерьевич; Филенко, Олеся Николаевна; Кобылянский, Б. Б. (Технологический центр, Украинский государственный университет железнодорожного транспорта, 2016)
Для удельной на единицу биомассы скорости окисления вредного вещества получено дифференциальное уравнение на макроуровне, описывающее кинетику биохимической деструктуризации. На основании феноменологического подхода к обобщению результатов стационарных лабораторных экспериментов предложена универсальная макрокинетическая математическая модель при субстратном ингибировании. Полученная модель предлагается в качестве базовой основы для количественного описания нестационарных процессов в установках биоочистки.

The results of stationary laboratory experiments are analyzed on the basis of the specific (per unit biomass) degradation rate of environmental pollutants. The presence of substrate inhibition for both gaseous, and water-dissolved pollutants is revealed. The phenomenological approach, which takes into account two obvious phenomena in a simple form: the contact of a microorganism with the substrate molecule and the inhibitory effect of the environment on it is applied to the analytical description of the relationship between the bio-oxidation rate and the pollution concentration. Numerical values of empirical coefficients of relationships for the investigated processes are calculated. The differential equation, describing the kinetics of biochemical degradation at the macro-level is proposed. The macrokinetic mathematical model of bioremediation is defined as a system of two functions, quantitatively reflecting the pollutant specific oxidation rate-concentration relationship and the concentration-time relationship, and satisfying the relationship of these parameters in a differential form. The concentration-time relationship is determined in the form of both the numerical integration algorithm and the approximate formula. The relevance and versatility of the proposed model for the investigated processes are proved. The resulting model is the basis for the quantitative description of non-stationary processes in bioreactors.
Development of universal model of kinetics of bioremediation stationary process with substrate inhibition
Keywords: биохимическая деструктуризация; удельная скорость окисления; феноменологический подход; субстратное ингибирование; biochemical degradation; specific oxidation rate; macrokinetic model; pollution concentration; phenomenological approach; substrate inhibition